The portable MBA in entrepreneurship - Bygrave, William D.; Zacharakis, Andrew (Hoboken, N.J : John Wiley & Sons, 2010)
A totally updated and revised new edition of the most comprehensive, reliable guide to modern entrepreneurship For years, the Portable MBA series has tracked the core curriculum of leading business schools to teach you everything you need to know about business-without the cost of earning a traditional MBA degree
Includes index
BSBA
Keywords: New business enterprises; Small business -- Management; Venture capital; Entrepreneurship